1997
DOI: 10.1080/10584589708221683
|View full text |Cite
|
Sign up to set email alerts
|

A critical study of defect migration and ferroelectric fatigue in lead zirconate titanate thin film capacitors under extreme temperatures

Abstract: The temperature dependence of the ferroelectric switching behavior was measured for lead zirconate titanate capacitors with the composition Pb(Zr,fjoTi.40)03. Results indicated that a temperature rise contributes to an increasing rate of logarithmic decay in the polarization during repeated switching reversals. Most c a n t theories dealing w i t h polarization degradation, known as fatigue, are based on the motion of defects. In support of this phenomena, where the decay rate R(T) is proportional to exp(AQ/kT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Indeed both improvement 18,42,43 and deterioration 44,45 of fatigue endurance at higher temperatures have been reported in the literature.…”
Section: Temperature Dependencementioning
confidence: 86%
“…Indeed both improvement 18,42,43 and deterioration 44,45 of fatigue endurance at higher temperatures have been reported in the literature.…”
Section: Temperature Dependencementioning
confidence: 86%
“…In spite of intensive studies in past decades, the low-temperature performance of ferroelectric thin films has not been understood as well as the room-temperature one. 1,2 Nevertheless, the temperature dependence of ferroelectric properties is one of the interesting issues, in view of not only technological applications, but also in a fundamental sense. 3 In fact, FRAM devices may undergo service at a low-temperature circumstance, such as in space.…”
mentioning
confidence: 99%
“…The effect of temperature obtained both from our simulation (curves) and the experimental result of Paton et al 31 (symbols) are shown in Fig. 8.…”
Section: Resultsmentioning
confidence: 97%